2013
DOI: 10.1038/ncomms4014
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the biodiversity of nanoscale signatures of spider silk fibres

Abstract: Living organisms are masters at designing outstanding self-assembled nanostructures through a hierarchical organization of modular proteins. Protein-based biopolymers improved and selected by the driving forces of molecular evolution are among the most impressive archetypes of nanomaterials. One of these biomacromolecules is the myriad of compound fibroins of spider silks, which combine surprisingly high tensile strength with great elasticity. However, no consensus on the nano-organization of spider silk fibre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…It is not easily clear the importance of this internal sensor data, but the 30 kDa cut-off membranes were statistically significant different (P < 0.05) from 3 kDa and 100 kDa UF membranes' data (Figure 4). The relevance of this data will be further explored when comparing a plethora of manmade and natural polymeric materials but some evidence suggest that it could be associated with morphological differences per se [7,8]. Ultrafiltration membranes of different cut-offs showed similar (P > 0.05) adhesion and energy dissipation average and RMS values (Figure 4).…”
Section: Resultsmentioning
confidence: 96%
“…It is not easily clear the importance of this internal sensor data, but the 30 kDa cut-off membranes were statistically significant different (P < 0.05) from 3 kDa and 100 kDa UF membranes' data (Figure 4). The relevance of this data will be further explored when comparing a plethora of manmade and natural polymeric materials but some evidence suggest that it could be associated with morphological differences per se [7,8]. Ultrafiltration membranes of different cut-offs showed similar (P > 0.05) adhesion and energy dissipation average and RMS values (Figure 4).…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies have revealed that the strength of silk fibers also relies on its hierarchical structure (Cranford et al, 2012;Koski et al, 2013;Qin and Buehler, 2013;Silva and Rech, 2013;Qin et al, 2015). The structure of a spider's web is hierarchical in two aspects: the protein secondary structure inside a single silk fiber is hierarchical and the geometric structure of the whole web is hierarchical.…”
Section: Development Of New Smart Materials and Applications Inspiredmentioning
confidence: 99%
“…This stems from the fact that spider silk fibres can surprisingly merge strong tensile strength and high elasticity which are similar to those observed for steel and nylon, respectively. The last few decades have been marked by an explosion of studies describing molecular, structural, and mechanical properties of spider silk fibres 1–11 . The major reason for this interest is that spider silk fibres are one of the most promising next-generation candidates for bioinspired polymers 12 .…”
Section: Background and Summarymentioning
confidence: 99%
“…A systematic proposal toward a rational use of nanoscale features of spider silk fibres was presented in our recent Nature Communications paper 1 . There, we explored the biodiversity of spider silk fibres by several atomic force microscopy (AFM) imaging and spectroscopic modes.…”
Section: Background and Summarymentioning
confidence: 99%